MATH LADDER SEBAGAI UPAYA MEMBANGUN MOTIVASI BELAJAR MATEMATIKA SISWA DI SMPN 1 JOMBANG - Ira Wahyu Wardani; Isti Qomariyah; Raden Sulaiman; Siti Rochmatin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Building motivation learning process is needed, learning motivation is the force individuals to learn knowledge and skills, especially subjects that students consider difficult such as mathematics. Mathematics subject that’s considered as difficult, so motivating students before learning is very useful for building positive representations in students mathematics learning. One way that can be used to build motivation’s with learning media. Math Ladder is learning media that can build students' motivation to learn mathematics. This media combines ladder with mathematics. The writing of this article aims as effort to build motivation learn mathematics students through Math Ladder. It’s expected that Math Ladder can reset thinking students who think mathematics boring and difficult to be more interesting and fun. This research method uses classroom action research. The results of this study state, Math Ladder can be effort in building motivation to learn mathematics in SMPN 1 Jombang.